F, UML Pelatihan Analisis dan Desain Sistem Informasi Menggunakan Unified Modeling Language (UML) di SMK Pelita Madani Kabupaten Pringsewu - Ferly Ardhy; Fitra Endi Fernanda; Ulfa Isni Kurnia; Alfina Alfina; Salman Alfarisi Salimu; Ockhy Jey Fhiter Wassalam; Ratnasari Ratnasari; Nur Aminudin; Rendy Yudha Pratama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Information system design is a stage of creating an information system. Based on the SDLC stages globally, the design is at stage 5. In the development of object-oriented programming techniques, a standardized modeling language for the development of software/information systems built using object-oriented programming techniques. the Unified Modeling Language (UML) emerged because of the need for visual modeling to specify, describe, build, and documentation of software systems/information systems. The Unified Modeling Language (UML) performs modeling in designing software systems/information systems. The purpose of this training is to implement the knowledge of lecturers to the community (students) by providing training in analyzing UML-based information systems in SMK Pelita Madani Pringsewu, with supporting tools using Star Uml. In the PKM was attended by 27 students of class XII, the participants get information system analysis and design materials, such as: Use Case Diagram, Activity Diagram, Sequence Diagram and class Diagram. The implementation of this training provide results: increasing the ability of participants to create business processes using Star Uml tools in the process of making applications / information systems.